Pathogenic mechanisms of Trichoderma hamatum, a postharvest pathogen causing fruit rot - Hai-Rui Wang; Xiong Xiong; Wen-Chao Li; Shuang-Jiao Ma; Yan-Xue Liu; Tong Liu; Ke-Xiang Gao; Chuan-Rong Li; Hui-Xiang Liu; Ye-Han Tian (Postharvest Biology and Technology, 2026)

Understory vegetation and soil microorganisms respond to afforestation on the Loess Plateau - Yunyin Xue; Ning Wang; Nan Gao; Lanxi Chen; Jun’e Liu; Rui Wang; Zhengchao Zhou (CATENA, 2026)

Interfacial electronic coupling in Bi2O3/COF heterostructures for high-performance supercapacitors - Rui Zhang; Hong-xia Gao; Yu-ting Zhao; Li Li; Yan Lv; Xue-yan Wu; Jixi Guo; Rui Xue (Chemical Engineering Journal, 2026)

CRISPR/Cas9 system inhibits largemouth bass virus infection in vitro and in vivo - Rui-Long He; Mao-sheng He; Xin-Yuan Jiang; Yi-Wang; Hao-Liang; Xiang-Yi Bu; Kun Xu; Fei Ling; Gao-Xue Wang; Hai-Feng Jiang (Aquaculture, 2026)

Bilayer encapsulation strategy enabled ultra-stretchable electronic skin for human-machine interaction - Miao Kong; Yuxin Chen; Shengwei Gao; Xue Wang; Jiaxin Zhuang; Panqi Huang; Zifan Li; Xu Wang; Zilin Wang; Yuqing Zhang; Ji Cheng; Ruiqi Guo; et al. (Chemical Engineering Journal, 2026)

Influence of Rate Effects on Fracture-Induced Opening of Interlayer Branch Fractures - Wen-rui Wang; Zong-qing Zhou; Hua-qing Ma; Xue-lin Zheng; Lei Chen; Cheng-lu Gao; Zhi-yuan Liu (Rock Mechanics and Rock Engineering, 2026)

Food-derived inositol derivatives mitigate high-fat diet-induced adiposity by attenuating inflammation and promoting adipocyte browning in mice - Xiaochen Guo; Mengjie Xu; Linlin Liu; Qinghui Lin; Rui Gao; Ruoxuan Xu; Wei Yu; Zhongmei Liang; Pengfei Wu; Zehan Dong; Zhen Xie; Nan Meng; et al. (Food Bioscience, 2026)

Influence of ecological factors on the accumulation of active substances in Camellia nitidissima - Xiao-Xia Zhao; Meng-Xue Su; Shuang-Shuang Li; Hui Gao; Guo-Yue Yan; Shu-Rui Wang; Yan-Yuan Bai; Yang-Jiao Xie (Plant Biosystems, 2026)

DICP1-A precisely degrades STING-A but not STING-B to suppress IFN expression through the autophagic pathway in gibel carp - Yue Wu; Shun Li; Fan-Xiang Gao; Zhi Li; Rui-Hai Gan; Can Zhang; Xiao-Li Yang; Zhuo-Cong Li; Chu-Jing Zhou; Yang-Yang Wang; Na Xu; Xue-Bing Wang; et al. (Aquaculture, 2026)

Sinomenine ameliorates experimental autoimmune neuritis by suppressing pro-inflammatory immune components and restoring immune balance - Yan-Mei Gong; Zhen-Lin Liu; Si-Miao Li; Yi-Fan Wei; Guo-Hui Gao; Rui-Qi Xu; Xue-Min Li; Yu-Dong Liu; Rui-Sheng Duan; Ying Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Hydrothermal-responsive plasmonic aerogel for dynamic 3D hotspot regulation and ultrasensitive SERS detection of dairy products contaminants - Jing-Xiang Wang; Zhi-Gao Xu; Xin-Rui Wang; Yao-Yao Zhang; Ri-Hui Su; Xin-Xin Zhang; Su-Ming Dai; Wei-Wei Zhu; Xue-Cai Tan; Ke-Jing Huang; Jun Yan (Analytica Chimica Acta, 2026)

Three-Dimensional Fast Marching Seismic Traveltime Computation Based on Coarse-Grid Interpolation - Yan-song Li; Jun-jie Yang; Xue-feng Gao; Hui Sun; Yun Long; Peng Lin; Song-da Ji; Hong-yong Ren; Rui Chen (Applied Geophysics, 2026)

Responses of ecological stability in subtropical coastal phytoplankton communities to varying N:P ratios under present and future scenarios - Jichen Chen; Yonglong Xiong; Jingke Ge; Xin Zhao; Yuan Feng; Xu Li; Chi Song; Xiao Yang; Rui Zhang; Jin-Yu Terence Yang; Wuchang Zhang; Shengyao Sun; et al. (Water Research, 2026)

Qualitative analysis of chemical constituents and study on the biological activity of Polygonum perfoliatum L - Chaochen Yue; Ya Zhang; Juan Xue; Tian Lu; Lei Li; Yanjie Wang; Rui Zhou; Di Gao; Huifang Chai (Natural Product Research, 2026)

Assessment of genetic diversity and pathogenicity of porcine rotavirus A, and immunogenicity of a bivalent inactivated vaccine in southern China - Guangli Hu; Zhiqing Zhao; Liguo Gao; Rui Geng; Shengjin Liu; Hao Zhang; Yongchang Cao; Hanqin Shen; Chunyi Xue (Veterinary Microbiology, 2026)

Genome-wide identification of the laccase gene family in wheat (Triticum aestivum L.) during Fusarium pseudograminearum infection - Li-Yu Chen; Yi Diao; Ju-Hong Ma; Xiang-Xue Zhang; Rui Li; Yan Liu; Hong-Tao Tang; Zhi Wang; Sha Gao; Rui-Huan Xu; Zhen-sheng Kang; De-Jun Han; et al. (Plant Science, 2026)

Effect of roasting on the chemical profiles of white and black sesame seeds during accelerated storage - Hao Liu; Shu-Guang Gao; Ming-Zhe Sun; Mei-Qi Yang; Huai-Yang Cao; Ke-Xin Zhang; Min-Shu Hong; Rui-Fu Cui; Zhao Qin; Hua-Min Liu; Xue-Ya Wang; Zhi-Jie Li (Food Chemistry, 2026)

Research on rock mechanics parameter prediction based on the frequency spectrum characteristics of vibration while drilling - Jia-kang Song; Jian-ning Wang; Zhao Ma; Yi-guo Xue; Rui-rui Cai; Fan-meng Kong; Lei Gao (Applied Geophysics, 2026)

Dietary components cooperate with intestinal flora to regulate food allergy - Jiaxi Yan; Li Niu; Wei Wang; Rui Gao; Jianxiong Hao; Huan Rao; Dandan Zhao; Xueqiang Liu; Wentong Xue; Yang Tian (Food Chemistry, 2026)

Ultrafast synthesis of Cu/Cu2O/Cu2S@coal-based carbon heterostructure with multiple redox pairs for enhancing specific capacitance in asymmetric supercapacitors - Hongxia Gao; Xueyan Wu; Yan Lv; Rui Xue; Fanze Meng; Peiqi Jing; Jixi Guo; Xiaogang Zhang (Chemical Engineering Journal, 2026)

Electric field-biochar integrated anammox system for high-efficiency nitrogen and phosphorus removal under elevated nitrogen concentration shock - Rui Hu; Xue Chen; Wanjiang Li; Yule Han; Shiliang Heng; Jiayi Wang; Yijing Gao; Xueqin Lu; Gang Luo; Shicheng Zhang; Guangyin Zhen (Chemical Engineering Journal, 2025)

A single chitosan-based fluorescent sensor for the discriminant analysis and quantitative detection of bisulfite and oxytetracycline in real samples - Chao Gao; Rui-Xue Li; Xiang Li; Zhenxing Zhong; Jia-Hui Wang; Wei Li (Carbohydrate Polymers, 2025)

Functional insights into JrWOX5: a WOX transcription factor regulating adventitious rooting and plant architecture in walnut - Rui-xue Gao; Pu Zhang; Ying-ying Chang; Li Song; Xiao-bo Song; Dong Pei (Plant Cell Reports, 2025)

Three-Dimensional Numerical Simulation of Vertical Bearing Behaviour of Snowflake Vinyl Plastic Pile - Lei Gao; Mohammad Biplab Mia; Ding Lu; Rui Xue; Xuejian Gao (Geotechnical and Geological Engineering, 2025)

A carrier-assisted strategy for accelerating aerobic granulation under low superficial gas velocity: Critical contributions of sediment biochar and camellia shell biochar carriers - Qingxia Lin; Chuxuan Song; Jun Li; Ziqiang Liu; Xue Hu; Rui Xue; Suiqin Yang; Yang Gao; Wei Zhang; Lean Zhou; Julong Sun; Jinting Wang; et al. (Environmental Research, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

Molecular detection and phylogenetic analysis of lumpy skin disease virus in Yunnan Province, China from 2019 to 2023 - Jun Yao; Xue Li; Lei Tan; Lin Gao; Pei Zhu; Jiarui Xie; Rui Yan; Taoyin Yu; Fengyi Xia; Qiyun Chen; Bangquan Zeng; Jiaping Yang (Veterinary Research Communications, 2025)

Two alkenyl phenol derivatives from the fungus Pestalotiopsis clavata JSQ 12 isolated from the mushroom Lanmaoa asiatica - Jing Tang; Rui Xu; Hao Ma; Shuai-Ming Zhu; Fu-Yao Luo; Xue Zhao; Ya-Shuai Kang; Yuan-Wei Gao; Yu Yang; Chang-Wei Li (Natural Product Research, 2025)

Bisphenol S promotes clear cell renal cell carcinoma progression by modulating the WNT5A-dependent EMT pathway - Hua Zhang; Fei Lin; Bo-Han Lin; Xiong-Lin Sun; Qing-Shui Zheng; Rui Gao; Yong Wei; Shao-Hao Chen; Xue-Yi Xue (Toxicology, 2025)

Size-dependent internalization of polystyrene microplastics as a key factor in macrophages and systemic toxicity - Wei-Qiang Luo; Meng-Ting Cao; Chen-Xuan Sun; Jun-Jian Wang; Meng-Xi Gao; Xue-Rui He; Le-Ning Dang; Yang-Yang Geng; Bing-Yao Li; Jing Li; Zhi-Cheng Shi; Xing-Rong Yan (Journal of Hazardous Materials, 2025)

Assessing the contribution of VOCs to SOA formation and identifying their key species during ozone pollution episodes in a typical petrochemical city - Xiaoyu Yan; Fuhong Gao; Yuanyuan Ji; Cong An; Rui Gao; Yanqin Ren; Junling Li; Xiaoshuai Gao; Likun Xue; Fanyi Shang; Jidong Li; Hong Li (Environmental Pollution, 2025)

Atmospheric carbonyls in urban Beijing in the summertime under the continuous implementation of clean air actions: Decreasing trends, source apportionments and new insights for control strategies - Xin Zhang; Fang Bi; Mingzhu Li; Lu Zhao; Hao Zhang; Yunfeng Li; Likun Xue; Rui Gao; Yujie Zhang; Xuezhong Wang; Zhenhai Wu; Zhanshan Wang; et al. (Journal of Cleaner Production, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Forest Microclimate as a Driver of Epiphytic Bryophyte Diversity Along a Subtropical Elevational Gradient - Zun Dai; Shi‐chen Xing; S. Robbert Gradstein; Min Li; Shu‐wen Tu; Xing Chen; Xue Yao; Shuang Gao; Rui‐ping Shi; Lu‐yan Tang; Ran Zhang; Zhao‐chen Zhang; et al. (Journal of Biogeography, 2025)
Aim Considering the importance of microclimate in maintaining the diversity of epiphytic bryophytes, we investigated epiphytic bryophytes along an elevational gradient in the subtropical forest of eastern China to unravel the diversity patterns of epiphytic liverworts and mosses along the elevational gradients and the roles of forest microclimates, topographic variables and host plant composition attributes in shaping these elevational diversity patterns. Location Tianmushan National Nature Reserve, Zhejiang, China. Taxon Epiphytic bryophytes. Methods Species diversity patterns of liverworts and mosses were compared based on an inventory of 16 plots along an elevational gradient from 367 to 1470 m. In situ microclimatic data of air temperature and moisture were collected under constant monitoring for over 3 years. Spatial linear models and structural equation models were used to assess the relative roles of the environmental variables in shaping the patterns of species diversity along elevation. Results We found that epiphytic liverwort and moss richness showed different elevational patterns; overall richness patterns of epiphytic bryophytes were largely driven by mosses. Epiphytic mosses exhibited a decline, followed by a hump‐shaped pattern of species richness with increasing elevation, while epiphytic liverworts showed a mid‐elevation plateau with a richness maximum between 800 and 1300 m. Forest microclimate, topography and host plant composition attributes influence epiphytic moss and liverwort patterns differently and interact in a complex way. Overall, species richness of epiphytic liverworts was most strongly affected by microclimate (mean annual air temperature of growing season) and of epiphytic mosses richness by topography (slope). Further, epiphytic liverwort species richness was more influenced by temperature than moisture. Main Conclusions This study highlights the importance of collecting climatic factors at a fine scale (microhabitats) for understanding the patterns and drivers of bryophyte diversity. Further, our findings demonstrate the differences between liverworts and mosses in terms of their response to different environments in the forest ecosystem.

Effective removal of Pb from industrial wastewater: A new approach to remove Pb from wastewater based on engineered yeast - Hao Luo; Zheng Su; Yang Liu; Dong-Fang Yuan; Rui Wang; Yu-Hang Ning; Dong-Jiao Zhang; Xian-Ke Chen; Zhao-Bao Wang; Xue-Yan Gao; Yue-Chao Zhang; Guang Cheng; et al. (Journal of Hazardous Materials, 2025)

Atomically dispersed iron & iron clusters synergistically accelerate electrocatalytic ammonia synthesis - Haoran Zhang; Yuelong Liu; Sanshuang Gao; Haijian Wang; Rui Bai; Yan Zhao; Yingtang Zhou; Guangzhi Hu; Xue Zhao (Chemical Engineering Journal, 2025)

Hexavalent chromium reduces testosterone levels by impairing lipophagy and disrupting lipid metabolism homeostasis: Based on a metabolomic analysis - Qian Xue; Le Zhang; Rui Wang; Jiayunzhu Xu; Chaofan Wang; Shidi Gao; Xin Fang; Chunyang Meng; Rifeng Lu; Li Guo (Toxicology, 2024)

Immune checkpoint-regulatable hydrogel-immobilized nanotherapeutics for post-surgical treatment of osteosarcoma - Da-Wang Zhao; Zhiliang Gao; Meng Si; Rui Hu; Xue Ma; Kaiwen Liu; Yixiang Zhao; Qiting He; Xiangzhen Kong; Chunwang Jia; Haoxin Zhai; Yuanqiang Zhang; et al. (Chemical Engineering Journal, 2024)

Correction to: Screening for ferroptosis genes related to endometrial carcinoma and predicting of targeted drugs based on bioinformatics - Rui Wang; Wei Lang; Qian Xue; Le Zhang; Yunzhu Xujia; Chaofan Wang; Xin Fang; Shidi Gao; Li Guo (Archives of Toxicology, 2024)

Screening for ferroptosis genes related to endometrial carcinoma and predicting of targeted drugs based on bioinformatics - Rui Wang; Wei Lang; Qian Xue; Le Zhang; Yunzhu Xujia; Chaofan Wang; Xin Fang; Shidi Gao; Li Guo (Archives of Toxicology, 2024)

Heterologous expression and characterization of two delta glutathione S-transferases genes involved in imidacloprid metabolism in Grapholita molesta - Qin-Wei Pang; Wen-Jie He; Ming-Gao Li; Ming Wang; Xue-Yao Zhang; Li-Jun Zhang; Ling-Ling Gao; Rui-Yan Ma; Yan-Qiong Guo; Qin Yu (Chemosphere, 2024)

Natural aromatic extract of black tea improved the water retention of pork meat batter - Wen-ping Xu; Rui-ling Dong; Ao-jing Lv; Yu-cong Li; Li-ting Zeng; Xue-ling Gao; Jun Qi; Zhou Lin; Hui-min Yan; Chun-hui Zhang; Guo-yuan Xiong (Food Research International, 2024)

Mantle-rooted fluid pathways and world-class gold mineralization in the giant Jiaodong gold province: Insights from integrated deep seismic reflection and tectonics - Li-Qiang Yang; Jun Deng; Liang Zhang; Ai-Hua Zhao; M. Santosh; Xue-Feng Yu; Wei Yang; Da-Peng Li; Wei Shan; Dong Xie; Xiang-Dong Liu; Xue Gao; et al. (Earth-Science Reviews, 2024)

A novel AP2/ERF transcription factor, NtERF10, positively regulates plant height in tobacco - Li Xu; Yong Xu; Jia-rui Jiang; Chang-xin Cheng; Wen-wu Yang; Le-le Deng; Qi-li Mi; Wan-li Zeng; Jing Li; Qian Gao; Hai-ying Xiang; Xue-mei Li (Transgenic Research, 2024)
Ethylene response factors have been shown to be involved in the effects of plant developmental processes and to regulate stress tolerance. The aim of this study was to recognize the regulatory mechanisms of ethylene response factors on tobacco plant height. In this study, a gene-edited mutant (ERF10-KO) and wild type (WT) were utilized as experimental materials. Transcriptome and metabolome analyses were used to investigate the regulatory mechanism of NtERF10 gene editing on plant height in tobacco. Here, through the analysis of differentially expressed genes (DEGs), 2051 genes were upregulated and 1965 genes were downregulated. We characterized the different ERF10-KO and WT plant heights and identified key genes for photosynthesis, the plant hormone signal transduction pathway and the terpene biosynthesis pathway. NtERF10 was found to affect the growth and development of tobacco by regulating the expression levels of the PSAA , PSBA , GLY17 and GGP3 genes. Amino acid metabolism was analyzed by combining analyses of differentially expressed genes (DEGs) and differentially accumulated metabolites (DAMs). In addition, we found that members of the bHLH, NAC, MYB, and WRKY transcription factor families have vital roles in regulating plant height. This study not only provides important insights into the positive regulation of the ethylene response factor NtERF10 on plant height during plant growth and development but also provides new research ideas for tobacco molecular breeding.

C-Phycocyanin improves the quality of goat oocytes after in vitro maturation and vitrification - Xing-Yue Wang; Yang Gao; Hao-Ran Liu; Teng Wang; Meng-Lei Feng; Fang-Rui Xue; Kang Ding; Qi Yang; Zhao-Yu Jiang; Dui Sun; Chun-Ru Song; Xiao-Jie Zhang; et al. (Theriogenology, 2024)

Genomic and transcriptomic analysis reveals the genetic diversity and adaptive signatures of Maduo sheep - Li-Na Chang; Xue Gao; Shi-Xin Wu; Rui-Dong Wan; Zhan-Xing Yang; Hai-Mei Zhao; Ke Zhang; Xin-Quan Zhao; You-Gui Fang; Gong-Xue Jia (Small Ruminant Research, 2024)

Two new sesterterpenoids from Atractylodes japonica Koidz. ex Kitam - Yuan-Yuan Zhou; Zhao Sun; Yan Liu; Zhen-Xing Fang; Hui-Rui Gao; Ning-Yu Liu; Xiao-Juan Zhang; Bing-You Yang; Hai-Xue Kuang (Journal of Natural Medicines, 2024)

Anthropogenic cycles of praseodymium in China: 2000–2020 - Shijiang Xiao; Yong Geng; Xue Rui; Ziyan Gao; Chang Su; Tianli Yao; Chen Zhong (Resources Policy, 2024)

Effective Cellulase Production by Trichoderma reesei Using Solid and Liquid Inducers Mixture with Varying Ratios - Muhammad Jawad; Shuxin Pan; Youduo Wu; Omama Rehman; Ying Zhang; Rui Xu; Quan Zhang; Huipeng Gao; Chuang Xue (Sugar Tech, 2024)

Comparison of the ozone formation mechanisms and VOCs apportionment in different ozone pollution episodes in urban Beijing in 2019 and 2020: Insights for ozone pollution control strategies - Yunfeng Li; Zhenhai Wu; Yuanyuan Ji; Tianshu Chen; Hong Li; Rui Gao; Likun Xue; Yafei Wang; Yuxi Zhao; Xin Yang (Science of The Total Environment, 2024)

A metabolomics discrimination-based strategy for screening the antithrombin active markers of perilla seeds: A natural oil crop - Suyi Liu; Xingyue Jin; Rui Wang; Xue Meng; Kunze Du; Jin Li; Xiumei Gao; Yanxu Chang (Food Chemistry, 2024)

The roles of Methylobacterium organophilum and Sphingomonas melonis for accelerating N-methyl pyrrolidone (NMP) biodegradation - Yongyi Gao; Ting Chen; Yifan Hou; Ruiyun Xue; Rui Liu; Fu Chen; Yongming Zhang; Bruce E. Rittmann (Journal of Water Process Engineering, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Ferrostatin-1-loaded thermosensitive nanodelivery system for noise-induced hearing loss treatment - Peng-Wei Ma; Pei-Heng Lu; Hao Yuan; Jia-Wei Chen; Wei Gao; Yu-Qiang Lun; Jia-Ning Guo; Xue-Rui Ding; Rui Liang; Si-Yu Li; Zi Wang; Wei-Long Wang; et al. (Chemical Engineering Journal, 2023)

Multiple stages of Au mobilization in the Changshagou Au deposit, Eastern Tianshan, NW China: Insights from mineral chemistry and fluid inclusions - Yi-Hao Liu; Yun Zhao; Chun-Ji Xue; Rui Wang; Hai-Xia Chu; Xiao-Bo Zhao; Matthew J. Brzozowski; Reimar Seltmann; Jun Chen; Jun-Bao Gao (Journal of Asian Earth Sciences, 2023)

Neurobehavioral disorders induced by environmental zinc in female zebrafish (Danio rerio): Insights from brain and intestine transcriptional and metabolic signatures - Fan Yu; Zhi-Shuai Hou; Hong-Rui Luo; Hong-Xia Li; Xue-Fan Cui; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Qin-Feng Gao; Jun Xiao; Pao Xu (Chemosphere, 2023)

Enhanced nitrate reduction by metal deposited g-C3N4/rGO/TiO2 Z-schematic photocatalysts: Performance and mechanism comparison of Pd-Cu and Ag - Houfen Li; Shuai Xue; Fang Cao; Cong Gao; Qian Wei; Rui Li; Aijuan Zhou; Sufang Wang; Xiuping Yue (Chemosphere, 2023)

Physicochemical Characterization of Three Active Pharmaceutical Ingredients for Compound Glycyrrhizin Solid Formulation and Compatibility Analysis via Thermal and Non-thermal Techniques - Xiang-yun Xie; Zhan-ying Chang; Chun-li Chen; Liang Zhang; Mei Wang; Cheng Tang; Hong-rui Xue; Xiao-li Gao (Journal of Pharmaceutical Innovation, 2023)

Selenium alleviates endoplasmic reticulum calcium depletion-induced endoplasmic reticulum stress and apoptosis in chicken myocardium after mercuric chloride exposure - Pei-Chao Gao; An-Qi Wang; Xue-Wei Chen; Han Cui; Yue Li; Rui-Feng Fan (Environmental Science and Pollution Research, 2023)

MiR-130/SNAP-25 axis regulate presynaptic alteration in anterior cingulate cortex involved in lead induced attention deficits - Tao Wang; Rui-Li Guan; Yun-Feng Zou; Gang Zheng; Xue-Feng Shen; Zi-Peng Cao; Rui-Hua Yang; Ming-Chao Liu; Ke-Jun Du; Xue-Hang Li; Michael Aschner; Ming-Gao Zhao; et al. (Journal of Hazardous Materials, 2023)

MicroRNA-588 regulates the invasive, migratory and vasculogenic mimicry-forming abilities of hypoxic glioma cells by targeting ROBO1 - Rui Yu; Rongrong Zhao; Xiaopeng Sun; Zongpu Zhang; Shaobo Wang; Xiao Gao; Zhongzheng Sun; Hao Xue; Gang Li (Molecular Biology Reports, 2023)
Background The microenvironment of hypoxia is an important factor contributing to the development of glioblastoma (GBM). MicroRNA-588 and its potential target Roundabout-directed receptor 1 (ROBO1) have been reported to promote tumor invasion and proliferation in diseases such as gastric, pancreatic and hepatocellular carcinoma, while their function in GBM and response to hypoxic states remain elusive. Methods A microarray was leveraged to identify differentially expressed microRNAs in U251 glioma cells cultured under normoxic and hypoxic conditions. The expression of miR-588 was assessed using quantitative real-time PCR (qRT‒PCR). Gain- and loss-of-function studies were used to evaluate the role of miR-588 under hypoxic and normoxic conditions. Cell invasion, migration, proliferation, and vasculogenic mimicry (VM) formation experiments were performed. The relationship between miR-588 and ROBO1 was confirmed using western blot and luciferase reporter assays. Intracranial xenograft tumor mouse models were used to study the function of miR-588 in vivo. Results The expression of miR-588 was significantly upregulated in hypoxic glioma cells relative to normoxic glioma cells. miR-588 inhibited the invasive, migratory and VM-forming abilities of glioma cells in vitro and in vivo. Mechanistically, roundabout guidance receptor 1 (ROBO1) is a direct, functionally relevant target of miR-588 in glioma. ROBO1 knockdown suppressed the expression of matrix metallopeptidase 2 (MMP2) and matrix metallopeptidase 9 (MMP9), thereby inhibiting the invasive, migratory and VM-forming abilities of glioma. Conclusions MiR-588 regulated the behaviors of hypoxic glioma cells by targeting ROBO1. miR-588 can be used as a prognostic marker for glioma and has potential implications in glioma gene therapy.

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Development and perspectives of rapid detection technology in food and environment - Xue-Xia Jia; Shuang Li; Dian-Peng Han; Rui-peng Chen; Zi-Yi Yao; Bao-an Ning; Zhi-Xian Gao; Zhen-Chuan Fan (Critical Reviews in Food Science and Nutrition, 2022)

Aberrant Gene Expression of Selenoproteins in Chicken Spleen Lymphocytes Induced by Mercuric Chloride - Jia-Hong Chu; Yu-Xue Yan; Xue-Wei Chen; Pei-Chao Gao; Lan-Xin Li; Rui-Feng Fan (Biological Trace Element Research, 2022)

Two new photoactive metal-organic compounds for degradation of methylene blue and treatment in ophthalmic local anesthesia - Xue-Song Gao; Rui-Qiang Sun (Journal of Fluorescence, 2022)

Two new dammarane-type triterpenoids from the green walnut husks of Juglans mandshurica Maxim - Yuan-Yuan Zhou; Hui-Rui Gao; Hong-Juan Song; Dan-Da Ma; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Xiao-Li Wang; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2022)

Effects of different energy diets on DNA methylation and mRNA expression in follicle stimulating hormone receptor gene promoter region of Duolang sheep during estrus - Bo Liu; Hongjian Li; Weikun Tao; Fei Huang; Xue Rui; Jie Wang; Peng Niu; Di Fang; Qinghua Gao (Molecular Biology Reports, 2022)

A multi-dosing regimen to enhance the spatial memory of normal rats with α5-containing GABAA receptor negative allosteric modulator L-655,708 - Congcong Yuan; An Gao; Qiang Xu; Beibei Zhang; Rui Xue; Yan Dou; Chunshui Yu (Psychopharmacology, 2021)

Summery Intra-Tidal Variations of Suspended Sediment Transportation – Topographical Response and Dynamical Mechanism in the Aoshan Bay and Surrounding Area, Shandong Peninsula - Yan Wang; Yanguang Dou; Liang Zou; Fei Gao; Dapeng Su; Rui Hu; Baojing Yue; Biying Xue (Journal of Ocean University of China, 2021)

Elevated pCO2 Impedes Succession of Phytoplankton Community From Diatoms to Dinoflagellates Along With Increased Abundance of Viruses and Bacteria - Ruiping Huang; Jiazhen Sun; Yunlan Yang; Xiaowen Jiang; Zhen Wang; Xue Song; Tifeng Wang; Di Zhang; He Li; Xiangqi Yi; Shouchang Chen; Nanou Bao; et al. (Frontiers in Marine Science, 2021)
Eutrophic coastal regions are highly productive and greatly influenced by human activities. Primary production supporting the coastal ecosystems is supposed to be affected by progressive ocean acidification driven by increasing CO 2 emissions. In order to investigate the effects of high p CO 2 (HC) on eutrophic plankton community structure and ecological functions, we employed 9 mesocosms and carried out an experiment under ambient (∼410 ppmv) and future high (1000 ppmv) atmospheric p CO 2 conditions, using in situ plankton community in Wuyuan Bay, East China Sea. Our results showed that HC along with natural seawater temperature rise significantly boosted biomass of diatoms with decreased abundance of dinoflagellates in the late stage of the experiment, demonstrating that HC repressed the succession from diatoms to dinoflagellates, a phenomenon observed during algal blooms in the East China Sea. HC did not significantly influence the primary production or biogenic silica contents of the phytoplankton assemblages. However, the HC treatments increased the abundance of viruses and heterotrophic bacteria, reflecting a refueling of nutrients for phytoplankton growth from virus-mediated cell lysis and bacterial degradation of organic matters. Conclusively, our results suggest that increasing CO 2 concentrations can modulate plankton structure including the succession of phytoplankton community and the abundance of viruses and bacteria in eutrophic coastal waters, which may lead to altered biogeochemical cycles of carbon and nutrients.

The substrate‐dependent regulatory effects of the AfeI /R system in Acidithiobacillus ferrooxidans reveals the novel regulation strategy of quorum sensing in acidophiles - Xue‐Yan Gao; Chang‐Ai Fu; Likai Hao; Xiu‐Feng Gu; Rui Wang; Jian‐Qiang Lin; Xiang‐Mei Liu; Xin Pang; Cheng‐Jia Zhang; Jian‐Qun Lin; Lin‐Xu Chen (Environmental Microbiology, 2021)
Summary A LuxI/R‐like quorum sensing (QS) system (AfeI/R) has been reported in the acidophilic and chemoautotrophic Acidithiobacillus spp. However, the function of AfeI/R remains unclear because of the difficulties in the genetic manipulation of these bacteria. Here, we constructed different afeI mutants of the sulfur‐ and iron‐oxidizer A . ferrooxidans , identified the N‐acyl homoserine lactones (acyl‐HSLs) synthesized by AfeI, and determined the regulatory effects of AfeI/R on genes expression, extracellular polymeric substance synthesis, energy metabolism, cell growth and population density of A . ferrooxidans in different energy substrates. Acyl‐HSLs‐mediated distinct regulation strategies were employed to influence bacterial metabolism and cell growth of A . ferrooxidans cultivated in either sulfur or ferrous iron. Based on these findings, an energy‐substrate‐dependent regulation mode of AfeI/R in A . ferrooxidans was illuminated that AfeI/R could produce different types of acyl‐HSLs and employ specific acyl‐HSLs to regulate specific genes in response to different energy substrates. The discovery of the AfeI/R‐mediated substrate‐dependent regulatory mode expands our knowledge on the function of QS system in the chemoautotrophic sulfur‐ and ferrous iron‐oxidizing bacteria, and provides new insights in understanding energy metabolism modulation, population control, bacteria‐driven bioleaching process, and the coevolution between the acidophiles and their acidic habitats.

α -Tetralone glycosides from the green walnut husks of Juglans mandshurica Maxim. and their cytotoxic activities - Yuan-Yuan Zhou; Shuang Guo; Ying Wang; Hong-Juan Song; Hui-Rui Gao; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2020)

Development of 19 novel microsatellite markers of lily-of-the-valley (Convallaria, Asparagaceae) from transcriptome sequencing - Qi-Xiang Lu; Jing Gao; Jun-Jie Wu; Xuan Zhou; Xue Wu; Meng-Di Li; Yu-Kun Wei; Rui-Hong Wang; Zhe-Chen Qi; Pan Li (Molecular Biology Reports, 2020)

Mouse adaptation of the H9N2 avian influenza virus causes the downregulation of genes related to innate immune responses and ubiquitin-mediated proteolysis in mice - Jing Guo; Xinxin Gao; Baotao Liu; Yubao Li; Wenqiang Liu; Jianbiao Lu; Cheng Liu; Rui Xue; Xuyong Li (Medical Microbiology and Immunology, 2020)

A new triterpene from the green walnut husks of Juglans mandshurica Maxim - Yuan-Yuan Zhou; Hong-Juan Song; Shuang Guo; Ying Wang; Hui-Rui Gao; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Bing-You Yang; Hai-Xue Kuang (Journal of Natural Medicines, 2019)

Hydrogen peroxide and nitric oxide are involved in programmed cell death induced by cryopreservation in Dendrobium protocorm-like bodies - Xue-ru Jiang; Rui-fen Ren; Wei Di; Meng-xue Jia; Ze-di Li; Yan Liu; Rong-fu Gao (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Nature and origin of Mesozoic granitoids and associated mineralization in the Sanjiang Tethys Orogeny, SW China: the Xiuwacu complex example - Xue Gao; Li–Qiang Yang; Rui–Gang Zhang; Jian–Ying Meng (International Geology Review, 2019)

Impact of Land Use Change on Hydrologic Processes in a Large Plain Irrigation District - Xiao-Bo Luan; Pu-Te Wu; Shi-Kun Sun; Xiao-Lei Li; Yu-Bao Wang; Xue-Rui Gao (Water Resources Management, 2018)

Lead Exposure Impairs Hippocampus Related Learning and Memory by Altering Synaptic Plasticity and Morphology During Juvenile Period - Tao Wang; Rui-Li Guan; Ming-Chao Liu; Xue-Feng Shen; Jing Yuan Chen; Ming-Gao Zhao; Wen-Jing Luo (Molecular Neurobiology, 2016)

Phylogenetic relationships and Y genome origin in Kengyilia (Triticeae: Poaceae) based on single copy gene DMC1 - Gang Gao; Zi-lin Tang; Jia-bin Deng; Xue-mei Gou; Qian Wang; Yan Zhang; Chun-bang Ding; Li Zhang; Yong-hong Zhou; Rui-wu Yang (Biologia, 2016)

Degradation of p-Nitrophenol in Soil by Dielectric Barrier Discharge Plasma - Rui Li; Yanan Liu; Yu Sun; Wenjuan Zhang; Ruiwen Mu; Xiang Li; Hong Chen; Pin Gao; Gang Xue; Stephanie Ognier (Water, Air, & Soil Pollution, 2015)

Effect of hydrogen sulfide on D1 protein in wheat under drought stress - Hua Li; Ming Quan Gao; Rui Li Xue; Dan Wang; Hui Jie Zhao (Acta Physiologiae Plantarum, 2015)

Phylogenetic relationships among Elymus and related diploid genera (Triticeae: Poaceae) based on nuclear rDNA ITS sequences - Gang Gao; Jia-bin Deng; Xue-mei Gou; Qian Wang; Chun-bang Ding; Li Zhang; Yong-hong Zhou; Rui-wu Yang (Biologia, 2015)

Optimal intervention time of vagal stimulation attenuating myocardial ischemia/reperfusion injury in rats - Qiang Wang; Rui-Ping Li; Fu-Shan Xue; Shi-Yu Wang; Xin-Long Cui; Yi Cheng; Gao-Pu Liu; Xu Liao (Inflammation Research, 2014)

Size distributions of aerosol sulfates and nitrates in Beijing during the 2008 Olympic Games: Impacts of pollution control measures and regional transport - Xinfeng Wang; Tao Wang; Ravi Kant Pathak; Mattias Hallquist; Xiaomei Gao; Wei Nie; Likun Xue; Jian Gao; Rui Gao; Qingzhu Zhang; Wenxing Wang; Shulan Wang; et al. (Advances in Atmospheric Sciences, 2013)

Isolation and characterization of microsatellite markers from Lagerstroemia caudata (Lythraceae) and cross-amplification in other related species - Ming Cai; Rui Meng; Hui-Tang Pan; Yi-Ke Gao; Ming Sun; Ping Song; Xue-Feng Wang; Qi-Xiang Zhang (Conservation Genetics Resources, 2010)